Association Between Iron Metabolism and Acute Kidney Injury in Critically Ill Patients With Diabetes - Mo, Manqiu; Gao, Yunqing; Deng, Ling; Liang, Yuzhen; Xia, Ning; Pan, Ling (Frontiers in Endocrinology, 2022)
Objective: Iron overload plays an important role in the pathogenesis of diabetes and acute kidney injury (AKI). The aim of this present study was to explore the relation between iron metabolism and AKI in patients with diabetes. Methods: Clinical data of diabetes patients from MIMIC-III database in intensive care unit (ICU) were retrospectively analyzed. The Regression analyses were used to explore the risk factors of AKI and all-cause death in critical patients with diabetes. The area under the receiver operating characteristic curves (AUROCs) were used to analyze serum ferritin (SF) and regression model to predict AKI in critical patients with diabetes. All diabetes patients were followed for survival at 6 months, and Kaplan-Meier curves were used to compare the survival rates in patients with different SF levels. Results: A total of 4997 diabetic patients in ICU were enrolled, with a male to female ratio of 1.37:1 and a mean age of 66.87±12.74 years. There were 1637 patients in AKI group (32.8%) and 3360 patients in non-AKI group. Multivariate Logistic regression showed congestive heart failure (OR=2.111, 95CI%=1.32-3.376), serum creatinine (OR=1.342, 95CI%=1.192-1.512), OASIS score (OR=1.075, 95CI%=1.045-1.106), increased SF (OR=1.002, 95CI%=1.001-1.003) and decreased transferrin (OR=0.993, 95CI%=0.989-0.998) were independent risk factors for AKI in critical patients with diabetes. Multivariate Cox regression showed advanced age (OR=1.031, 95CI%=1.025-1.037), AKI (OR=1.197, 95CI%=1.011-1.417), increased SOFA score (OR=1.055, 95CI%=1.032-1.078), and increased SF (OR=1.380, 95CI%=1.038-1.835) were independent risk factors for 6-month all-cause death in critical diabetic patients. The AUROC for SF and regression model to predict AKI in critical patients with diabetes were 0.782 and 0.851, respectively. Kaplan-meier curve showed the 6-month survival rate in SF increased group was lower than that in SF normal group (log-rankχ2=16.989, P<0.001). Conclusion: Critically ill diabetic patients with AKI were easily complicated with abnormal iron metabolism. Increase of SF is an important risk factor for AKI and all-cause death in critically ill patients with diabetes.